Interleukin-17A Is Associated With Alveolar Inflammation and Poor Outcomes in Acute Respiratory Distress Syndrome. Issue 3 (March 2016) - Mikacenic, Carmen; Hansen, Elizabeth E.; Radella, Frank; Gharib, Sina A.; Stapleton, Renee D.; Wurfel, Mark M.
Abstract : Objective: Interleukin-17A is a proinflammatory cytokine known to play a role in host defense and pathologic inflammation in murine models of lung injury. The relationship between interleukin-17A and inflammation in human lung injury is unknown. Our primary objective was to determine whether interleukin-17A levels are associated with alveolar measures of inflammation and injury in patients with acute respiratory distress syndrome. Our secondary objective was to test whether interleukin-17A levels are associated with acute respiratory distress syndrome–related outcomes. Design: Observational study. Setting: Six North American medical centers. Patients: We studied two groups of patients with acute respiratory distress syndrome: 1) patients previously enrolled in a placebo-controlled clinical trial of omega-3 fatty acids performed at five North American medical centers ( n = 86, acute respiratory distress syndrome 1), and 2) patients with systemic inflammatory response syndrome admitted to an ICU who developed acute respiratory distress syndrome ( n = 140, acute respiratory distress syndrome 2). In acute respiratory distress syndrome 1, we used paired serum and bronchoalveolar lavage fluid samples obtained within 48 hours of acute respiratory distress syndrome onset, whereas in acute respiratory distress syndrome 2, we used plasma obtained within the first 24 hours of ICU admission. Interventions: None. Measurements and Main Results: We measured circulating interleukin-17A in acute respiratory distress syndrome 1 and acute respiratory distress syndrome 2. We also measured interleukin-17A, neutrophil counts, and total protein in bronchoalveolar lavage fluid from acute respiratory distress syndrome 1. We found that bronchoalveolar lavage interleukin-17A was strongly associated with higher bronchoalveolar lavage percent neutrophils ( p < 0.001) and bronchoalveolar lavage total protein ( p < 0.01) in acute respiratory distress syndrome1. In both acute respiratory distress syndrome 1 and acute respiratory distress syndrome 2, elevated interleukin-17A was associated with higher Sequential Organ Failure Assessment scores ( p < 0.05). Conclusions: Elevated circulating and alveolar levels of interleukin-17A are associated with increased percentage of alveolar neutrophils, alveolar permeability, and organ dysfunction in acute respiratory distress syndrome. Abstract : Supplemental Digital Content is available in the text.